2020
DOI: 10.1111/edt.12607
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical characterization of primary teeth pulp stem cells from three stages of resorption in serum‐free medium

Abstract: Background/Aims: Dental pulp stem cells from primary teeth cultured in serum-free conditions may have clinical use for the repair and regeneration of teeth as well as other complex tissues and organs. The aim of this study was to test the change in the stem cell markers expression/ stem cell population in human primary pulp cells at the different stages of root resorption. Methods: Caries-free human primary canines at defined stages of physiological root resorption were included (n = 9). In vitro cultures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
(94 reference statements)
1
8
0
Order By: Relevance
“…DPSC are known to derive from neural crest cells and are inclined to differentiate into neural cells [ 36 ]. DPSC have a higher positive ratio for neural markers such as NES, GFAP, and s100-beta than other kinds of MSC [ 5 , 36 , 70 , 71 ]. However, PDLSC have different embryonic origin: dental pulp is formed from dental papilla while PDLSC originate from dental follicle cells [ 7 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPSC are known to derive from neural crest cells and are inclined to differentiate into neural cells [ 36 ]. DPSC have a higher positive ratio for neural markers such as NES, GFAP, and s100-beta than other kinds of MSC [ 5 , 36 , 70 , 71 ]. However, PDLSC have different embryonic origin: dental pulp is formed from dental papilla while PDLSC originate from dental follicle cells [ 7 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…SHED isolation efficiency was 100% and we observed no contamination during cell cultivation. Alansary, et al 19 (2020) collected teeth with different levels of root resorption and observed contamination in the culture of half of the samples, even using antibiotics and antimycotics. The authors claimed that teeth with advanced root resorption have a higher chance of contamination during cultivation.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Studies observed a lower expression of CD105 in SHED, an important marker of the panel suggested by the ISCT. 2 , 19 21 This low expression is possibly due to the time of teeth collection (stages of root resorption) and the different isolation and culture methods. According to Alansany, et al 19 (2020), the lowest expression of CD105 occurs in cells grown in serum-free conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rowlands et al also state that premolar eruption can be predicted from CRR [ 48 ]. The current lines of research analyse the morphological changes of the pulp cells [ 49 ] and ultrastructural alterations in the pulp tissues [ 50 ] during the different stages of physiological root resorption, which will help to better understand this process.…”
Section: Discussionmentioning
confidence: 99%